Associações entre síndrome metabólica, inflamação, índices do estado nutricional e de distribuição de gordura corporal em pacientes em hemodiálise crônica - Vogt, Barbara Perez [UNESP] (2013)
Since 1998, eight definitions for the diagnosis of metabolic syndrome (MS) have been proposed by institutions and/or groups of experts, in order to correctly identify individuals exposed to increased cardiovascular risk. The existence of multiple definitions for the diagnosis of MS is difficult to determine their prevalence rates. Regardless of the guideline used for diagnosis, the frequency data show that SM is a big public health problem worldwide and the number of people affected is increasing. This is due to increased rates of obesity, particularly visceral obesity, which is considered a key element in the development of MS. The production of adipokines by visceral adipose tissue is the factor that links obesity to insulin resistance (IR). To assess IR, the euglycemic hyperinsulinemic clamp is considered the gold standard methodology, but the homeostatic model assessment can be used for this purpose, because it is already validated method. Body fat and its distribution has great influence on the IR, and its evaluation has strong correlation with IR. Imaging tests such as computed tomography and magnetic resonance imaging are important tools in research body composition in humans, because they allow the accurate and precise measurement of visceral and subcutaneous fat located in the abdominal region. Anthropometric measurements can also be used to assess obesity, by presenting low cost, safety and simplicity in implementation. Anthropometric measures of obesity seem to be associated with metabolic changes related to IR and stand out as noninvasive indicators for the risk assessment of IR, both in epidemiological research and clinical practice. They are: sagittal abdominal diameter, abdominal circumference, neck circumference, conicity index, waist-height, body mass index, body fat percentage, waist-hip ratio, waist-hip ratio and sagittal index. In the general population, MS is associated with high cardiovascular mortality, which is ...